If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1n + -2 = -15 Reorder the terms: -2 + -1n = -15 Solving -2 + -1n = -15 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1n = -15 + 2 Combine like terms: -2 + 2 = 0 0 + -1n = -15 + 2 -1n = -15 + 2 Combine like terms: -15 + 2 = -13 -1n = -13 Divide each side by '-1'. n = 13 Simplifying n = 13
| p-6u+3-4u+9p+14= | | -0.15x^2+150x=11000 | | -2=3+5x | | -0.15x^2+150x= | | x(x+4)=-20 | | 10(-0.2)+4=2(2) | | 3u+2u=25 | | 2(42x+2y)x(52x+3y)-(33x+6y)= | | 10(-0.4)+4=2(2) | | 21+7g=98 | | 15n^2+3n=0 | | -3(k-12)=48 | | 5x+12+6x-10=120 | | 10(-2.5)+4=2(2) | | 7x+3+72=180 | | 3+5+x-3=6+8-3+1 | | 63=12+b | | Cos^2(x)-3cosx+2=0 | | 3+w=5+7w | | 1=-8+3b | | 2(5x+5)=9x+8 | | 8x-5=93 | | 360=230+67+x | | -2(-1y+-5)=8 | | -2+6(1-7k)=24 | | Y-1=x-6 | | x+9f+10=5jforx | | (3x^2-5x+7)+(4x^2+9x-1)= | | 13+6x-5=4x+8 | | 3h-(-8)=14 | | 2x+-1=1 | | 10x=8x+8 |